Rancang Bangun Sistem Informasi Penjualan Pada Mina Market Benowo - Yhufti Avissa; Puji Arifin Widodo; Teguh Susanto (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Mina market Benowo franchise is managed by the orphanage Uswah. Currently the sales information system used by mina market only generate sales summary information obtained from a copy of the bill of sale in one period. These conditions resulted in a decrease in sales because there is no sales information, while managers need information that can be used to evaluate sales activities.From the above problems is proposed sales information system that can be used to manage the entire sales data. So that the information system can generate the information needed to support decision-making takes place in mina market. the manager who needs information that the sales report, report the percentage of sales of goods statement items and expired goods report.This system can generate sales reports that provide information regarding sales received for the specified period, report the percentage of sales of these items provide information regarding sales of goods of interest to the customer based on the specified period missal periods per week or per month, a statement for this item provides information about how many times the goods are held back and the number of times the goods are sold in a particular period and expired goods report displays information about the number of goods that are approaching expiration date of goods. Keyword : Sales Information System, Sales, Stock